The transcription factor ERG regulates a low shear stress-induced anti-thrombotic pathway in the microvasculature - C. Peghaire (Nature Portfolio, 2019)
The endothelium actively maintains an anticoagulant surface through expression of thrombomodulin. Here, Peghaire et al. identify an anti-thrombotic pathway that controls thrombomodulin expression selectively in regions of low shear stress, via cooperation of the transcription factors ERG and KLF2.